Pengembangan Multimedia Interaktif Melting pada Materi Perubahan Wujud Zat untuk Siswa Kelas IV SDN Semen 1 - Haris Prasetyo; Wahyudi Wahyudi; Aprilia Dwi Handayani (YASIN, 2026)
Although Natural and Social Sciences (IPAS) learning on changes in states of matter in elementary schools has been supported by various learning media, students’ low understanding of abstract concepts remains a major obstacle, especially when the media used are still limited to textbooks, pictures, and instructional videos. This study aims to develop MELTING (Media Learning Interactive) interactive multimedia on the topic of changes in states of matter for fourth-grade students at SDN Semen 1 and to determine its levels of validity, practicality, and effectiveness. This study used the Research and Development method with the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of media experts, material experts, fourth-grade teachers, and fourth-grade students at SDN Semen 1. Data were collected through observation, interviews, questionnaires, and learning outcome tests, then analyzed using quantitative descriptive methods. The results show that MELTING interactive multimedia obtained a validity level of 86%, categorized as very valid, based on assessments by media and material experts. The practicality test results showed a percentage of 93%, categorized as very practical, based on teacher and student responses. In addition, the effectiveness test results showed an improvement in students’ learning outcomes, with an N-gain score of 0.56, which falls into the moderate category. The conclusion of this study affirms that MELTING interactive multimedia is feasible for use as a learning medium on changes in states of matter for fourth-grade elementary school students. The implications of this study show that interactive multimedia can serve as an effective alternative learning medium for improving students’ conceptual understanding and learning outcomes in abstract subject matter.